Pathogenicity of goose astrovirus genotype 2 in chickens - Dalin He; Xiaoning Jiang; Maoquan Tian; Xing Niu; Feng Wei; Bingrong Wu; Ling Gao; Yi Tang; Youxiang Diao (Poultry Science, 2023)
ABSTRACT: Goose astrovirus genotype 2 (GAstV-2) is the causative agent causing severe visceral gout and joint gout in goslings, with mortality rates of affected flocks up to 50%. To date, continuous GAstV-2 outbreaks still pose a great threat to goose industry in China. Although most researches on GAstV-2 have focused on its pathogenicity to geese and ducks, limited studies have been performed on chickens. Herein, we inoculated 1-day-old specific pathogen-free (SPF) White Leghorn line chickens with 0.6 mL of GAstV-2 culture supernatant (TCID50 10−5.14/0.1 mL) via orally, subcutaneously and intramuscularly, and then assessed the pathogenicity. The results revealed that the infected chickens presented depression, anorexia, diarrhea, and weight loss. The infected chickens also suffered from extensive organ damage and had histopathological changes in the heart, liver, spleen, kidney, and thymuses. The infected chickens also had high viral load in tissues and shed virus after the challenge. Overall, our research demonstrates that GAstV-2 can infect chickens and adversely affect the productivity of animals. And the viruses shed by infected chickens can pose a potential risk to the same or other domestic landfowls.